Uji Kelembapan dan Evaluasi Mutu Fisik Sediaan Masker Serbuk Basis Tepung Limbah Biji Buah Durian - Wiranata, Neisca; Tutik, Tutik (Innovative: Journal Of Social Science Research, 2024)
Durian fruit seeds have benefits for the body, especially on facial skin because durian fruit seeds contain collagen which helps moisturize and prevent premature aging of facial skin. Besides its potential as food flour, durian seeds can also be used as cosmetic products. This study aims to determine the powder mask based on durian seed waste flour can meet the standards of physical quality evaluation and moisture test in accordance with Indonesian National Standards (SNI). The method used is quantitative. Powder masks were made with 3 formulations with concentrations of 12.5%, 25% and 50%. The powder masks were evaluated for physical quality (organoleptic, homogeneity, pH, specific gravity, spreadability, adhesiveness, drying time) and moisture test of the preparation. The test was carried out for 2 weeks with 2 applications each week. Data analysis using One Way ANOVA and physical quality evaluation data on adhesiveness and drying time obtained Sig < 0.05 which means there is no significant relationship. As for the results of pH, specific gravity, moisture test spreadability obtained Sig> 0.05 which means there is a significant relationship. Thus it can be concluded that the durian seed waste flour base powder mask does not meet the physical quality evaluation requirements in accordance with the Indonesian National Standard (SNI) and the moisture test meets the standard (SNI) can increase the moisture value of the skin.